Even mild cases of paediatric Henoch‐Schönlein purpura nephritis show significant long‐term proteinuria. (29th July 2014) - Tudorache, Elena; Azema, Christine; Hogan, Julien; Wannous, Hala; Aoun, Bilal; Decramer, Stéphane; Deschênes, Georges; Ulinski, Tim
Abstract Aim Henoch‐Schonlein purpura (HSP) is a common cause of paediatric renal disease in children, representing 10–15% of paediatric glomerulonephritis. This study examined the long‐term outcome of biopsy‐proven HSP nephritis to identify correlations between disease development and treatment. Methods Patients from three French centres were retrospectively analysed. Results We followed up 142 patients aged from 2 to 10.5 years with HSP nephritis, graded according to the International Study Group of Kidney Disease in Childhood classification. Mean (±SD) age at presentation was 7.6 ± 2.8 years. Nephrotic range proteinuria was present in 28% of patients with Grade II lesions, 60% with Grade III and 90% with Grade IV. Significant proteinuria (>0.5 g/L) was found in nine of 48 patients 3 years after renal biopsy, eight of 25 patients after 5 years and three of 14 patients after 10 years. There was no correlation between the proteinuria risk at 3, 5 or 10 years and the initial histological lesion or treatment modality. Treatment with angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers (ACEi/ARB) was linked to lower proteinuria, especially if it was started precociously. Conclusion Even mild forms of HSP nephritis risk significant long‐term proteinuria. Very early introduction of ACEi/ARB may improve the long‐term outcome independent of histological lesions.